2018
DOI: 10.1111/1440-1630.12519
|View full text |Cite
|
Sign up to set email alerts
|

What are the attributes of excellence in an acute practice occupational therapist?

Abstract: Background/aim: There is anecdotal recognition within the profession that novice occupational therapists who perform well at interview do not necessarily make the best practising clinicians. Further anecdotal evidence suggests that it is difficult to tell (at interview) which occupational therapists will follow which path and whether further training can achieve excellence in existing staff. What is it that makes the difference? What attributes do those truly 'excellent' clinicians have that makes them better … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 33 publications
0
3
0
Order By: Relevance
“…An Australian study aimed to identify the perception of occupational therapists about attributes required for an excellent performance with adults in the context of hospitalization. This study identified that the ability to communicate effectively was the professionals most valued attribute, as it allowed, among other aspects, the construction of the relationship with the user, a greater understanding of the activities performed and a greater understanding of the needs of the subject served (Swan et al, 2019).…”
Section: -Valuing Psychoemotional Aspectsmentioning
confidence: 99%
“…An Australian study aimed to identify the perception of occupational therapists about attributes required for an excellent performance with adults in the context of hospitalization. This study identified that the ability to communicate effectively was the professionals most valued attribute, as it allowed, among other aspects, the construction of the relationship with the user, a greater understanding of the activities performed and a greater understanding of the needs of the subject served (Swan et al, 2019).…”
Section: -Valuing Psychoemotional Aspectsmentioning
confidence: 99%
“…The selection of appropriate students is crucial for medical education; in addition to knowledge, students suitable for medical schools and professions must possess speci c personality traits and attitudes, including lifelong active learning, self-discipline, altruism, adaptability, and compassion. [14][15][16] These personality traits and attitudes cannot be assessed using written tests. 17,18 When recruiting medical students, medical school authorities must pay attention to their personality traits and attitudes in addition to their knowledge.…”
Section: Introductionmentioning
confidence: 99%
“…Training in interviewing and goal setting, empowerment and advocacy, using formal tools and clinical experience can all support the therapist, especially when working with challenging client groups (e.g., brain injury) and within organizational and other contextual barriers to client-centeredness (Barclay, 2002;Hunt, Le Dorze, Trentham, et al, 2015;McAndrew et al, 2000;Leach et al, 2010;Prescott et al, 2018;Prescott et al, 2019;Thyer et al, 2019). Not many studies to date explored the differences between expert occupational therapists and novices (Hodgetts et al, 2007;Swan et al, 2019). However, it has been recognized that there are significant differences in the clinical reasoning and decision-making practices of those two groups (Kuipers & Grice, 2009;Lui et al, 2000).…”
Section: Introductionmentioning
confidence: 99%